The geochemistry of Natural waters surface and groundwater environments - Drever, James I. (Estados Unidos | ESTADOS UNIDOS Prentice-Hall / Washington D. C, 1997)
This is an examination of both theoretical and practical approaches to the geochemistry of natural waters with more emphasis on fresh-water environments, environmental issues and regulatory requirements than in the previous edition. This text features a new chapter on contaminant transport modelling, a section on organic contaminants and a chapter on adsorption. There are more worked examples and end-of-chapter problems.
Sin Especificar
Keywords: Geoquímica | Química del agua | Hidrogeología